Influenza vaccine effectiveness estimates for Western Australia during a period of vaccine and virus strain stability, 2010 to 2012 - Levy, A.; Sullivan, S.; Tempone, S.; Wong, K.; Regan, Annette; Dowse, G.; Effler, P.; Smith, D. (Elsevier, 2014)
During 2010–2012 the strain composition of the influenza vaccine in the Southern Hemisphere did not change, but the circulating virus type/subtype did. We pooled data for these years from the Western Australian sentinel medical practice surveillance system for influenza to estimate vaccine effectiveness (VE) by influenza virus type and subtype. A case test-negative design was used with VE estimated as (1-odds ratio) × 100%. There were 2182 patients included in the analysis across the 3 years studied. The predominant subtype was A/H1pdm09 in 2010 and 2011, and A/H3 in 2012. The overall adjusted VE estimate against all influenza for 2010–2012 was 51% (95% CI: 36, 63). Estimates were highest against A/H1pdm09 at 74% (95% CI: 47, 87), followed by 56% (95% CI: 33, 71) for influenza B and lowest against A/H3 at 39% (95% CI: 13, 57). When analyses were restricted to compare influenza-positive patients with patients who tested positive for a non-influenza virus, overall adjusted VE was 59% (95% CI: 39, 72). These results suggest moderate protection against influenza by vaccination in Western Australia over the period 2010–2012, and are consistent with findings from other settings.